The physics of interlayer exciton delocalization in Ruddlesden–Popper lead halide perovskites - Giovanni, David (2021)
Two-dimensional (2D) lead halide Ruddlesden–Popper perovskites (RPP) have recently emerged as a prospective material system for optoelectronic applications. Their self-assembled multi quantum-well structure gives rise to the novel interwell energy funnelling phenomenon, which is of broad interests for photovoltaics, light-emission applications, and emerging technologies (e.g., spintronics). Herein, we develop a realistic finite quantum-well superlattice model that corroborates the hypothesis of exciton delocalization across different quantum-wells in RPP. Such delocalization leads to a sub-50 fs coherent energy transfer between adjacent wells, with the efficiency depending on the RPP phase matching and the organic large cation barrier lengths. Our approach provides a coherent and comprehensive account for both steady-state and transient dynamical experimental results in RPPs. Importantly, these findings pave the way for a deeper understanding of these systems, as a cornerstone crucial for establishing material design rules to realize efficient RPP-based devices.